Percutaneous Vertebroplasty and Facet Blocking for Treating Back Pain Caused by Osteoporotic Vertebral Compression Fracture - Yongquan Cheng; Xiaoliang Wu; Jiawei Shi; Hui Jiang (Pain Research and Management)
Background and Objectives. Back pains associated with osteoporotic vertebral compression fractures (OVCFs) may arise not just from vertebral body but also from posterior elements. Percutaneous vertebroplasty (PVP) and facet blocking (FB) combined therapy would relieve pain better, but it has not been elucidated. The purpose of this retrospective study was to compare the treatment effects of PVP and FB combined therapy with PVP alone in OVCFs patients. Methods. Clinical and radiological data of 204 patients were reviewed. The patients were divided into Group A (PVP alone) and Group B (PVP and FB combined therapy) according to treatments. Back pain was evaluated with Visual Analog Scale (VAS) and Oswestry Disability Index (ODI). The operation, fluoroscopic exposure time, and bone cement leakage were recorded. The χ2 test, Student’s t-test, and repeated measures analysis of variance were used to compare the differences between the two groups. Results. There were 125 patients in Group A and 79 patients in Group B. Their baseline characteristics were similar (P>0.05). The mean VAS scores of Group A and Group B were 7.03 and 7.21 at admission, 4.7 and 3.2 at 1 day after operation, 4.0 and 3.0 at 3 months, and 2.2 and 2.2 at 12 months after operation, respectively. The mean ODI scores of Group A and Group B were 30.9 and 29.8 at admission, 17.6 and 17.7 at 3 months, and 10.5 and 10.9 at 12 months after operation, respectively. The mean operation time and fluoroscopic exposure time of Group A (35.6 minutes and 7.2 seconds, respectively) was significantly shorter than that of Group B (45.7 minutes and 11.7 seconds, respectively, P<0.01). The incidence of bone cement leakage and new fractures after operation did not have statistically significant difference between groups. Conclusion. PVP and FB combined therapy could provide better pain relief than PVP alone in short term after operation in patients with OVCFs associated back pains.